Author unknown - Geue, Tom (Harvard University Press, 2019)
Introduction: Literature unmastered – Part I. The power of the name: Name power – Tongue ties: Ovid's Ibis – A play without names: Octavia – Part II. The universal no-name: Phaedrus by name – Poet seeks patron: an open letter from me to you, or Numerosa Laus – The timeless pastoral of Calpurnius Siculus – Part III. Whence and when: Whence: sources, frames, contexts – Historical transcendence – Conclusion: Unknowing literature
Keywords: Anonymous writings; Latin / History and criticism; Latin literature / Authorship